The use and effectiveness of adaptive servo ventilation in central sleep apnea: a study of consecutive sleep clinic patients. (22nd February 2020) - Huseini, Taha; McArdle, Nigel; Jasper, Emily; Kurmagadda, Sasya; Douglas, Jane; King, Stuart; Sturdy, Gavin; Singh, Bhajan
Abstract: The use of adaptive servo ventilation to treat central sleep apnea in the clinical setting is incompletely understood and could be under‐utilized. We reviewed our experience of adaptive servo ventilation use in patients with central sleep apnea. This study shows the effectiveness of adaptive servo ventilation in treating patients with central sleep apnea, irrespective of a predisposing factor, as assessed during a 4‐week treatment trial. Results show that adaptive servo ventilation was effective and superior to continuous positive airway pressure in controlling central sleep apnea and improving symptoms. Only a small proportion of these patients had comorbid heart failure. Early treatment with adaptive servo ventilation may improve long‐term adherence to therapy. These findings highlight the utility of adaptive servo ventilation in the management of central sleep apnea.